Порівняльне дослідження становища середньоазійських мігрантів у Росії та Абхазії - Брусіна, О. (Народна творчість та етнографія, 2010)
В статье сравнивается положение мигрантов из Узбекистана, Таджикистана и Киргизстана в Абхазии и России. В частности, в то время, как в Абхазии эти мигранты чувствуют себя в основном хорошо, в России, где им пришлось работать ранее, они подвергались притеснениям со стороны чиновников, правоохранительных органов и националистов. Среднеазиатские мигранты, занятые в Абхазии преимущественно в сфере услуг, строительства и благоустройства, сохраняют обособленность от местного населения и в подавляющем большинстве собираются, заработав денег, вернуться на родину, откуда их вытолкнула безработица и низкий уровень жизни. There is a comparison of the status of the migrants from Uzbekistan, Tajikistan and Kyrgyzstan in Abkhazia and Russia in the article. While these migrants mainly feel good in Abkhazia, they had been testing the oppressions from the officials, the law and nationalists in Russia where they had to work till then. The Middle East migrants are engaged mainly in the spheres of public services, building and city improvement in Abkhazia, they stay apart from the natives and predominantly intend to return with the earnings to the motherland from which they had been forced out due to unemployment and low standard of living.